Reputation: 33
I need a little help with creating a recurrence relation for the Basic Operation for the following recursive algorithm:
int D(int n) {
if (n==0) {
return 0;
}
return D(n - 1) + D(n - 1);
}
I think the basic operation for this is addition but I am having trouble setting up the recurrence relation
Upvotes: 0
Views: 637
Reputation: 77837
Are you sure this is the correct code? The recurrence relation is
D(n) = 2 * D(n-1)
base case D(n) = 0
Do you see how this works? The function's recursion step shows you the recurrence step; the function's termination clause shows you the base case.
I'm worried because in closed form, this is
D(n) = 0 for all n
Upvotes: 1